Effect of Spatial Arrangement and Variety on Performance of Common Bean (Phaseolus Vulgaris L) in Western Kenya - J. N , Mafuta; E. O , Auma; L , Ngode (African Journal of Education,Science and Technology (AJEST), 2017)
Dry common bean is one of the most important food security pulse crops produced in Kenya. Its production is limited by a number of agronomic practices including spatial crop arrangement. A study was conducted from March to June 2016 at Mabanga ATC in Bungoma and University of Eldoret in Uasin Gishu Counties to determine the suitable field spatial arrangement for optimum bean yield. Three bean varieties (Canadian wonder, KAT B1 and Rose coco) were studied under the following spatial arrangement: 60 cm x 15 cm, 45 cm × 20 cm, 36 cm × 25 cm and 30 cm × 30 cm. Randomized complete block design replicated three times was used to conduct the experiment on both sites. Data was collected on plant height, number of flowers per plant, pods per plant, seeds per pod, 1000 seed weight and seed weight/hectare. Data was subjected to ANOVA in GENSTAT software and means separated by Tukey’s HSD at p≤ 0.05. The results indicated significant differences due to spatial arrangement on plant height in Mabanga site only. There were significant differences on number of pods, number of seeds per pod, 1000 seed weight and seed weight/hectare (kg/ha) in both sites. It is concluded that the spatial arrangement of 30 cm × 30 cm and 36 cm × 25 cm gave better yield in Mabanga while a spatial arrangement of 36 cm × 25 cm and 45 cm × 20 cm gave better yield in terms of 1000 seed weight at University of Eldoret. In this study spatial arrangement of 30 cm × 30 cm and 36 cm × 25 cm is therefore recommended for farmers within Bungoma County (Mabanga) while 36 cm × 25 cm and 45 cm × 20 cm recommended for farmers within Uasin Gishu County (University of Eldoret).